The Essence of Liberalism in the Light of Values Construction and Religious Study - Huang, Paulos (Journal of Research for Christianity in China (JRCC), 2025)
This article is to make a reflection on the liberalism in the light of values construction and Christian studies. I have done this through three metaphors to describe the context of liberalism in the contemporary China. I call the State a Leviathan, which has positive function in protecting people but has also negative influence in pressing the mass. The New Leftists in the contemporary China proclaim to fight for the weak class of people and for the justice and equality, but they are easily to become the drivers and helpers of the Leviathan to destroy all powers which may threaten the State. Liberalists in contemporary China are like a wild horse, which can bring many benefits to the state and its people since it is alive and longing for liberty, but it can also easily fall into disorder and chaos because of its breaking all kinds of restrictions. Thus, it is important to refer to the transcendent viewpoint of Christianity so as to avoid absolutism and idolism. The main contribution which Christianity can give to the debate between new leftism and liberalism is to offer a totally new value system and a new structure of knowledge.